STUDY THE INFLUENCE OF TECHNOLOGY USE IN LEARNING ON STUDENT LEARNING MOTIVATION: A LITERATURE REVIEW - Sakyanti, Ida; Rahmattullah, Rahmattullah; Akmaluddin, Akmaluddin (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This literature review explores the influence of technology use in learning on student learning motivation. In recent years, the rapid advancement of technology has transformed educational landscapes, providing innovative tools and resources that enhance the teaching and learning experience. This review synthesizes findings from various studies to examine how different forms of technology—such as digital learning platforms, interactive applications, and multimedia resources—impact student motivation across diverse educational settings. The research indicates that technology can significantly enhance student engagement by promoting interactivity and personalization in the learning process. Moreover, incorporating technology into the classroom fosters a collaborative learning environment, encouraging peer interaction and support. Additionally, the availability of instant feedback through technological tools helps students identify their strengths and weaknesses, thereby motivating them to improve their performance. However, challenges such as digital divide, varying levels of access to technology, and the risk of distraction are also addressed in this review. The findings suggest that while technology has the potential to positively influence motivation, its effectiveness largely depends on how it is integrated into the curriculum and the overall approach taken by educators. In conclusion, this literature review highlights the significant role that technology plays in enhancing student learning motivation. It calls for educators and policymakers to develop strategic frameworks for implementing technology in educational settings to maximize its benefits while mitigating associated challenges.